TINDAK TUTUR DIREKTIF DALAM IKLAN KATU PERDANA GSM - Anil Saputri; Novia Juita; Ngusman Ngusman (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purposes of this research were is describe the, (1) variety of directive speech act in GSM first card advertisement; (2) function of speech act in GSM first card; (3) speech act in GSM first card; (4) speech situation context in GSM first card. The data of this research is directive speech act in GSM first card advertisement. The source of this research is speech act in GSM first card advertisement. The data were collected by using listening method and writing technique. Finding of the research is five kind of directive speech act, they are asking, requesting, giving suggestion, giving advice, and denying. Four speech act function are competitive, gratify, cooperation, and contradiction. Four kind speech strategies are speaking admittedly without platitude, speaking admittedly with positive gentlemen platitude, speaking admittedly with negative gentlemen platitude, and speaking obscurely. Twelve speech situation contexts are in speech situation context (+K+S+P), tends to be used BTTB speaking strategy; in speech situation (+K+S-P), (+K-S-P), (=K+S+P), (=K+S-P), (-K+S+P), and (-K-S+P), tends to be used BBKP speaking strategy; in speech situation (+K-S+P), and (=K-S-P), tends to be used BBKN speaking strategy; and in speech situation (=K-S+P), (-K+S-P), and (-K-S-P), tends to be used BBS speaking strategy.